Macroprudential regulation and leakage to the shadow banking sector - Stefan Gebauer; Falk Mazelis (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Macroprudential policies for financial institutions have received increasing prominence since the global financial crisis. These policies are often aimed at the commercial banking sector, while a host of other non-bank financial institutions, or shadow banks, may not fall under their jurisdiction. We study the effects of tightening commercial bank regulation on the shadow banking sector. For this purpose, we develop a DSGE model that differentiates between regulated, monopolistically competitive commercial banks and a shadow banking system that relies on funding in a perfectly competitive market for investments. After estimating the model using euro area data from 1999-2014 including information on shadow banks, we find that tighter capital requirements on commercial banks increase shadow bank lending, which may have adverse financial stability effects. Coordinating the macroprudential tightening with monetary easing can limit this leakage mechanism, while still bringing about the desired reduction in aggregate lending. We discuss how regulators that either do or do not consider credit leakage to shadow banks set policy in response to macroeconomic shocks. Lastly, in a counterfactual analysis, we then compare how a macroprudential policy implemented before the crisis on all financial institutions, or just on commercial banks, would have dampened the leverage cycle.
Keywords: E58; F45; G23; G28; 330; Macroprudential Regulation; Monetary Policy; Shadow Banking; Non-Bank Financial Institutions; Financial Frictions